Design and Development of an Efficient CGPA Calculator for Accurate Academic Assessment (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The goal of the CGPA Calculator is to create a trustworthy and efficient Cumulative Grade Point Average (CGPA) calculator to help students evaluate their academic achievement. This paper uses Java's powerful GUI frameworks for a user-friendly interface. C is used for backend calculations, and its numerical and data handling skills are used. The software calculates CGPA with 99% accuracy across grading systems, improving user engagement and computation time. The application saves time and helps students make academic selections based on accurate CGPA ratings. CGPA Calculator automates the calculation of pupils' cumulative academic performance. The calculator calculates SGPA and CGPA from course grades and credit hours. The application avoids manual errors and gives students a fast, reliable way to track their academic performance by streamlining the computation process. The CGPA calculator can be linked to institutional grading systems and customized to credit-based and other scales. It provides real-time updates and thorough data to improve academic tracking and analysis. This paper includes a CGPA Calculator to simplify student academic performance calculations. Students and instructors can track academic progress accurately and efficiently with the calculator, which calculates CGPA using subject grades and credit hours. The calculator, written in Python, Java, or other languages, can handle many semesters, different grading scales, and cumulative scores. This application lets students understand their academic position and helps schools standardize GPA calculation. User-friendliness, precision, and adaptability make the paper suitable for other educational systems.